Una palabra esencial. Genealogía histórica del término culture (siglos XVI-XVIII) - Goberna Falque, Juan R. (Anales de Filología Francesa, 2010)
Terminological researches, among lexical analysis, are also an endless topic of study for researchers in every field of humanities and social sciences, be they economists, sociologists, political scientists, anthropologists or historians. When they devote their efforts to starting linguistic, terminological, lexicographical or conceptual studies, they can use different methods and consider, in general, either point of view: they can try to study or, what is the same, “dissect” the vocabulary associated with a short historical period, defined with great precision, or they can deal with the genealogy of one or more lexical terms they consider to be essential words from a historical perspective. As a matter of fact we have taken this last contextual approach in this brief contribution on the emergence of figurative meanings of the term culture and his widespread in France between the 16th and 18th centuries.